2017
DOI: 10.1111/ases.12392
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ventral hernia repair

Abstract: The management of ventral hernia is continuously evolving as it responds to new demands and new technology in surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
0
19
0
7
Order By: Relevance
“…This tension on the tissues is important to discuss since it has been implicated as the cause of many operative failures. 9 Ramirez et al found a partial solution for this issue in 1990 with the description of a myofascial release, or component separation, of the external oblique muscle from the lateral edges of the rectus abdominis. 15 This maneuver allows for added laxity of the midline, leading to less strain on the fascia when brought back together.…”
Section: Component Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…This tension on the tissues is important to discuss since it has been implicated as the cause of many operative failures. 9 Ramirez et al found a partial solution for this issue in 1990 with the description of a myofascial release, or component separation, of the external oblique muscle from the lateral edges of the rectus abdominis. 15 This maneuver allows for added laxity of the midline, leading to less strain on the fascia when brought back together.…”
Section: Component Separationmentioning
confidence: 99%
“…This chapter reviews the terminology, technique, outcomes, and future directions of retromuscular sublay repairs while explaining why this operative procedure took several years to become popular despite its original description more than 50 years ago. 8,9 Nomenclature Conceptually, a sublay repair can be thought of as mesh placement in a pocket formed anterior to the peritoneum and posterior to the rectus abdominis. 10 However, misperception of the nomenclature arises due to the several terms used (often interchangeably), to describe mesh placement in this tissue plane-such as retromuscular, retrorectus, preperitoneal, and Rives-Stoppa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В истории хирургии вентральных грыж было несколько важных этапов. Один из них связан с применением синтетических имплантатов, другойс появлением сепарационных пластик, к третьему этапу можно заслуженно отнести внедрение эндовидеохирургических методов лечения [13,14]. Эру малоинвазивных технологий в хирургии вентральных грыж в 1993 г. начал французский хирург K. LeBlanc.…”
Section: Introductionunclassified
“…With an ageing [2] and increasingly obese [3] population, the risk of incisional hernia post midline laparotomy has increased, from 8% in 1980 to 16% in 2012 [4]. Recurrence after a previous hernia repair is also high, with minimal improvement over the last 30 years [5]. VHs that repeatedly recur, have a wide ventral defect or are contaminated are known as complex VHs, and successful repair is extremely challenging [6].…”
Section: Introductionmentioning
confidence: 99%